2003
DOI: 10.1162/089892903321208169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pitch Sensitivity in Individuals with Autism: A Signal Detection Analysis

Abstract: Abstract& Past research has shown a superiority of participants with high-functioning autism over comparison groups in memorizing picture -pitch associations and in detecting pitch changes in melodies. A subset of individuals with autism,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
301
6
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(336 citation statements)
references
References 37 publications
(36 reference statements)
23
301
6
6
Order By: Relevance
“…Several studies had already found enhanced simple lowlevel visual processing (O'Riordan et al 2001;Plaisted et al 1998) and spared (Spencer et al 2000;Blake et al 2003) or diminished complex low-level visual processing (Milne et al 2002). In the auditory domain, enhanced simple low-level processing had been reported for pitch discrimination and chord disembedding (Bonnel et al 2003;Heaton 2003), in which perceptual performance depends on spectral processing. Using a complex low-level auditory task, Alcantara also found diminished temporal but intact spectral processing in children with autism (Alcantara et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies had already found enhanced simple lowlevel visual processing (O'Riordan et al 2001;Plaisted et al 1998) and spared (Spencer et al 2000;Blake et al 2003) or diminished complex low-level visual processing (Milne et al 2002). In the auditory domain, enhanced simple low-level processing had been reported for pitch discrimination and chord disembedding (Bonnel et al 2003;Heaton 2003), in which perceptual performance depends on spectral processing. Using a complex low-level auditory task, Alcantara also found diminished temporal but intact spectral processing in children with autism (Alcantara et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The EPF model predicts that A1-mediated perceptual processing will be superior in autism. Indeed, superior low-order auditory perception has been reported in experimental paradigms involving pitch perception (Bonnel et al 2003) and chord segmentation (Heaton 2003). However, few studies assessing complex low-level perceptual tasks in the auditory domain that require extensive neural integration have yet been conducted (Teder-Salejarvi et al 2005;Alcantara et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies used a similar adaptive staircase procedure (as we did) to assess pure tone pitch processing (Bhatara et al 2013;Bonnel et al 2010;Jones et al 2009). The first psychoacoustic evidence for enhanced pitch discrimination of pure tones was provided by Bonnel et al (2003), who observed superior pitch discrimination in adolescents with autism and in adults meeting full criteria for autism but not in those with Asperger syndrome (Bonnel et al 2010). Partial support for this finding was provided by Jones et al (2009), who found no differences in frequency discrimination at the group level, but who identified a subgroup of adolescents with ASD and delayed language onset who showed exceptional frequency categorization.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent observations concerns the evidence for enhanced pitch perception in children on the autistic spectrum and in a subgroup of adolescents and adults with ASD, especially those with early developmental language delay and language-related difficulties (O'Connor 2012). Superior pitch processing has been established regardless of stimulus complexity (e.g., for pure tones, complex tones, contours, nonwords, words and sentences) using a variety of psychophysical tasks (e.g., identification, discrimination, categorization, memory and labeling) (e.g., Bonnel et al 2003Bonnel et al , 2010Heaton 2005;Heaton et al 2008a, b, c;Järvinen-Pasley and Heaton 2007;Jones et al 2009;O'Riordan and Passetti 2006;Stanutz et al 2014). The majority of research using event-related potentials (ERP) also revealed enhanced neural detection of frequency changes in ASD at the pre-attentive level (using mismatch negativity or MMN) (e.g., Ferri et al 2003;Gomot et al 2002;Kujala et al 2007; but see Jansson-Verkasalo et al 2003; see Haesen et al 2011 for an extensive recent review of the psychophysical and electrophysiological literature on auditory processing in ASD).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence for lateralization of temporal and pitch processing in speech perception (for a recent review, see Zatorre & Gandour, 2008). Some studies indicate that temporal processing of auditory (including speech) input may be impaired in ASD (e.g., Cardy, Flagg, Roberts, Brian, & Roberts, 2004; Groen, van Orsouw, ter Huurne, Swinkels, van der Gaag, Buitelaar, et al, 2009), while pitch sensitivity may be a relative strength (e.g., Bonnel, Mottron, Peretz, Trudel, Gallun, E., & Bonnel, 2003). It is possible that inter-hemispheric underconnectivity in ASD (e.g., Just, Cherkassky, Keller, & Minshew, 2004) plays an additional role, resulting in poor coordination of pitch and temporal processing, thereby undermining any indirect benefit bestowed on temporal processing by intact pitch processing.…”
Section: Discussionmentioning
confidence: 99%